Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1002/jssc.201700340
|View full text |Cite
|
Sign up to set email alerts
|

Purification of polysaccharide from artificially cultivated Anoectochilus roxburghii (wall.) Lindl . by high-speed counter current chromatography and its antitumor activity

Abstract: To establish a systematic method for the extraction, purification, characterization and antitumor activity study of polysaccharide from artificially cultivated Anoectochilus roxburghii (wall.) Lindl. (AC-ARPS). High-speed counter current chromatography with two-phase aqueous systems was successfully applied to purify AC-ARPS after one-step separation. The purity of the AC-ARPS obtained by phenol/sulfuric acid method was 95.01%. The chemical structures of AC-ARPS were identified by a series of analytical method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…4 In recent decades, many studies have shown that A. roxburghii, as a Chinese folk medicine, has diverse pharmacological effects and medicinal properties, such as hepatoprotection, [5][6][7][8][9] anti-diabetes, 10,11 antifatigue, 12 antiosteoporosis, 9,13,14 vascular protective, 15 antioxidation, 16,17 and antitumor. 18,19 Some scholars have applied advanced and efficient technologies in the extraction, separation, and structural characterization of the active ingredients from A. roxburghii because of its curative effects. In recent years, the research team of the authors has conducted an in-depth exploration of the active components of A. roxburghii.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…4 In recent decades, many studies have shown that A. roxburghii, as a Chinese folk medicine, has diverse pharmacological effects and medicinal properties, such as hepatoprotection, [5][6][7][8][9] anti-diabetes, 10,11 antifatigue, 12 antiosteoporosis, 9,13,14 vascular protective, 15 antioxidation, 16,17 and antitumor. 18,19 Some scholars have applied advanced and efficient technologies in the extraction, separation, and structural characterization of the active ingredients from A. roxburghii because of its curative effects. In recent years, the research team of the authors has conducted an in-depth exploration of the active components of A. roxburghii.…”
Section: Introductionmentioning
confidence: 99%
“…10,27,28 For example, the polysaccharide from artificially cultivated A. roxburghii has been reported to possess antitumor effects. 19 However, little information has been published in terms of purification and structural characterization of the polysaccharide from A. roxburghii and its effects on CCl 4induced liver injury by in rats thus far. Some reports are available on the hepatoprotective effects of A. roxburghii from the different genera of the same family.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anoectochilus roxburghii contains flavonoids, 3,4 polysaccharides, 5 kinsenoside, 6 alkaloids, 7 sterols, 8 organic acids, 9 amino acids, trace elements, cardiac glycosides, and other active ingredients 10,11 . This herb is also referred to as ‘Golden Grass,’ ‘King of Medicine,’ and ‘Magic pill’ because of its diverse pharmacological effects, including antihyperglycemia, 12 antitumor, 13 anti‐inflammatory, 14,15 antioxidation, 16,17 and hepatoprotection 18,19 …”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is extremely economically valuable (Ye et al 2017). It is not only one of the original plants used in Traditional Chinese Medicine for diabetes (Cui et al 2012), tumors (Yu et al 2017), hyperpiesia (An et al 2014) and hepatitis (Zeng et al 2017), but it also has ornamental, cosmetological, culinary and other beneficial uses (Zhang et al 2015;Shao et al 2014). And aromatic and medicinal plants have been used for therapeutic, religious, cosmetic, nutritional, and beautification purposes since ancient times and humanity of all civilizations and culture are familiar with their usage (Ersoy et al 2017;Abramovic et al 2018;Tiwari et al 2018).…”
Section: Introductionmentioning
confidence: 99%